THE EFFECTIVENESS OF DIGITAL TAX ADMINISTRATION ON COMPLIANCE COSTS AND TAX COMPLIANCE OF MSME TAXPAYERS - Maharani, Husnunnida (Assets : Jurnal Ekonomi, Manajemen dan Akuntansi, 2025)
The Directorate General of Taxes has responded to technological advancements by implementing digital tax administration policies, namely e-filing, e-billing, and e-invoicing. The implementation of these policies is expected to reduce compliance costs and enhance taxpayer compliance, particularly among micro, small, and medium enterprises (MSMEs). The purpose of this study is to examine the effect of e-filing, e-billing, and e-invoicing on compliance costs and MSME taxpayer compliance. This research develops the Theory of Planned Behavior (TPB) and refines previous studies by incorporating compliance cost as an additional variable. Data were collected through a survey using questionnaires. Partial Least Squares (PLS) was employed as the analytical tool. The findings reveal that e-filing, e-billing, and e-invoicing have a negative effect on compliance costs, indicating that the implementation of digital tax administration reduces compliance costs. Furthermore, this study demonstrates that compliance costs positively influence the improvement of taxpayer compliance. These results can assist the Directorate General of Taxes in assessing the effectiveness of digital tax administration policies in reducing compliance costs and enhancing taxpayer compliance among MSMEs.